Penggunaan Teknik Komunikasi Antar Personal dalam Penguatan Imunisasi: Use of Interpersonal Communication Techniques in Strengthening Immunization - Baharuddin, Dharina; Arlianti, Nopa; Syahirah, Arifah; Septiani, Riza; Wardiati, Wardiati; Na’imah, Na’imah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The government in Indonesia continues to focus its attention on the problem of stunting (shortness). In 2022, the prevalence of stunting was 31.2%. Meanwhile, in Aceh Besar Regency's Atong Village, 5% of children under the age of five were stunted. Infectious disease is one of the stunting risk factors that immunization can help avoid. Therefore, the aim of executing this community service in Atong village is to raise the community's knowledge and awareness of child vaccination in the future. The method conducted was Inter-Personal Communication (KAP), which has an instructional and engaging model. The implementation employed instructive entertaining games and songs to demonstrate the efficacy of immunization and its schedule. The respondents included adults and the elderly who will support childhood immunization today and in the future. The activity lasted one day and began with an introductory game, followed by listening to one another in the form of a critical thinking stage about the types of diseases that children suffer from, a stage of finding ways to maintain children's health, a learning stage about types of immunizations, and a commitment stage to carry out routine immunizations. There were 60 persons in attendance, and all of them were quite enthusiastic about learning. The KAP approach was successful in getting people interested in learning about immunization. KAP strategies should be used in various sensitive educational settings in the community.